Experiments on norm focusing and losses in dictator games - Windrich, Ivo; Kierspel, Sabrina; Neumann, Thomas; Berger, Roger; Vogt, Bodo (Frontiers in Sociology, 2022)
We conducted experiments on norm focusing. The tests were carried out with two versions of dictator games: in one version of the game, the dictator had to allocate a gain of €10, while in the other version, a loss of €−10 needs to be allocated. In a first treatment, we focused subjects on the average giving in similar previous dictator games. The second treatment focused subjects on the behaviour of what a self-interested actor should do. In total, N = 550 participants took part in our experiments. We found (1) a significant difference in giving behaviour between gain and loss treatments, with subjects being moderately more self-interested in the loss domain, (2) a significant effect of focusing subjects on the average behaviour of others, but (3) no effect of focusing subjects on the behaviour of self-interested actors.